Brasil. Realizações 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
IICA has negotiated and approved two new projects, five addendums, and revisions of current projects with the Brazilian government and multilateral financing organizations. The portfolio covers various themes related to the Medium-Term Plan of the IICA and is prioritized by national and international institutions related to family farming, rural development policies, access to water, rural connectivity, digital innovation, climate change, biodiversity, cooperativism, gender, youth, sanitation, environmental, social and governance practices (ESG), productive chains, territorial development, animal biotechnology, agribusiness health, bioeconomy, and forest inventory. The IICA has partnered with organizations such as the Ministry of Agriculture, Livestock, and Supply, the Ministry of Regional Development, and the Brazilian Agency for Cooperation. Additionally, the IICA has held virtual technical dialogues and organized a technical mission to Brazil by a group of 21 Paraguayans to learn about water resource management, among other activities. The IICA has also organized the Spanish Rural Women Award.